Measurement and Chebyshev spectral analysis of Brownian coordinate of electrochemical noise. (1st December 2020) - Klyuev, A.L.; Davydov, A.D.; Grafov, B.M.
Highlights: Discrete Chebyshev spectroscopy for electrochemical analog of Brownian motion. Measurement of Chebyshev spectra of electrochemical coordinate of Brownian particle. Chebyshev power spectral density measured for Brownian coordinate of corrosion noise. Trend-resistant method for analysis of Brownian coordinate of electrochemical noise. Abstract: For the first time, the electrochemical Brownian motion is considered in the context of discrete Chebyshev spectroscopy. The computer processing of output signal of analog-to-digital converter operating in the first-order sinc filter mode enables measuring the discrete Chebyshev spectrum of electrochemical analog of Brownian particle coordinate. It is shown that there is the Chebyshev power spectral density with respect to the normalized Chebyshev polynomial degree. The Chebyshev power spectral density is determined for the Brownian coordinate of corrosion noise and for the Brownian coordinate of intrinsic noise of EVAL-AD7176-2SDZ evaluation board with a shorted input. For the first time, it is shown that the Chebyshev power spectral density for the Brownian coordinate of electrochemical noise depends on the first-order sinc filter output data rate. The trend-resistant method of Chebyshev power spectral density of Brownian coordinate can be used for the noise diagnostics of electrochemical devices and processes.